Antenatal sonographic diagnosis of choledochal cyst: Case report and imaging review. Issue 9 (13th December 2014) - Jensen, Kyle K.; Sohaey, Roya
ABSTRACT In this report, we present the antenatal two‐ and three‐dimensional sonographic findings from a fetus with choledochal cyst as well as confirmatory postnatal MRI. A delayed diagnosis of choledochal cyst is common, leading to significant morbidity and mortality. Visualizing bile ducts entering a right upper quadrant cyst is pathognomonic, and early diagnosis can facilitate definitive treatment with Roux‐en‐Y hepaticojejunostomy. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound43:581–583, 2015